A multicenter comparison of cognitive-behavioral therapy and interpersonal psychotherapy for bulimia nervosa. - Agras, W; Walsh, T; Fairburn, C; Wilson, G; Kraemer, H (2000)
BACKGROUND: Research suggests that cognitive-behavioral therapy (CBT) is the most effective psychotherapeutic treatment for bulimia nervosa. One exception was a study that suggested that interpersonal psychotherapy (IPT) might be as effective as CBT, although slower to achieve its effects. The present study is designed to repeat this important comparison. METHOD: Two hundred twenty patients meeting DSM-III-R criteria for bulimia nervosa were allocated at random to 19 sessions of either CBT or IPT conducted over a 20-week period and evaluated for 1 year after treatment in a multisite study. RESULTS: Cognitive-behavioral therapy was significantly superior to IPT at the end of treatment in the percentage of participants recovered (29% [n=32] vs 6% [n=71), the percentage remitted (48% [n=53] vs 28% [n = 31]), and the percentage meeting community norms for eating attitudes and behaviors (41% [n=45] vs 27% [n=30]). For treatment completers, the percentage recovered was 45% (n= 29) for CBT and 8% (n= 5) for IPT. However, at follow-up, there were no significant differences between the 2 treatments: 26 (40%) CBT completers had recovered at follow-up compared with 17 (27%) IPT completers. CONCLUSIONS: Cognitive-behavioral therapy was significantly more rapid in engendering improvement in patients with bulimia nervosa than IPT. This suggests that CBT should be considered the preferred psychotherapeutic treatment for bulimia nervosa.